Analytical model for the prediction of the piezoresistive behavior of CNT modified polymers. (15th January 2017) - Panozzo, Francesco; Zappalorto, Michele; Quaresimin, Marino
Abstract: In this work a theoretical and experimental study is carried out on the piezoresistive behavior of CNT modified polymers. A novel and easy-to-be applied analytical model is developed, to predict the piezoresistive response of CNT modified polymers, where the conductive network of CNTs within the polymeric matrix is modelled accounting for the three-dimensional random orientation of the nanofiller, the CNT waviness and entangling, and the electrical properties of the material in the undeformed state. Then, the analytical estimations are compared with the results from new experimental tests on specimens made of multi-walled CNT modified thermosetting matrix as well with data taken from the literature, showing a good agreement.